Healing the Incurable? Pentecostal Prayer Camps and Healing of Chronic Illnesses in Ghana - Benyah, Francis Ethelbert Kwabena (Mission studies, 2024)
Healing is one of the distinctive features of the Pentecostal movement. In Pentecostal missiology healing is fundamental and is geared towards the transformation of the human person and society. Healing thus encompasses both physical and spiritual ailments. It also concerns the healing of unjust structures of society – inequality, corruption, bad governance, and so on. In this article I examine some of the plausible factors that make persons living with chronic illnesses go to prayer camps in search of solutions for their illnesses. The article highlights how prayer camps in Ghana help those living with chronic illnesses negotiate their sense of self and identity in the midst of persistent illness. It argues that in a situation where healthcare systems cannot provide a cure for an illness, people identify with and rely on religious institutions and their resources such as those the prayer camps produce for support, meaning, and enhancement.